(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article explores the linguistic dichotomy of "good" and "bad" in English and Uzbek cultures. It analyzes how these concepts are represented in language, including their semantic fields, metaphorical usage, and socio-cultural implications. A comparative analysis is conducted using linguistic data, proverbs, idioms, and discourse patterns. The study employs qualitative and quantitative methods to identify commonalities and differences in the perception and expression of these concepts across the two languages.